PENGARUH KNOWLEDGE SHARING DAN FAKTOR DEMOGRAFI TERHADAP KINERJA PEGAWAI - Apri Anggita; Warsito Kawedar (Diponegoro Journal of Accounting, 2017)
This study aims to examine the relationship between knowledge sharing, demographic factors (age, education level, position, tenure) on employee performance. This research was conducted in 12 Regional Work Unit of Regency/ City in Central Java with 104 employees. Sampling technique in this research use purposive sampling. Statistic analysis used to analyze data using Structural Equation Modeling (SEM) with software Amos version 22.0. The results showed that knowledge sharing, education level, tenure have a positive and significant effect on employee performance. While the age factor has a positive and insignificant effect on employee performance, and position factor of employees have a negative and insignificant effect on performance.